2014
DOI: 10.1111/cfs.12161
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in child welfare intervention rates: the intersection of deprivation and identity

Abstract: A B S T R AC TChild welfare systems internationally exhibit very large inequalities in a variety of dimensions of practice, for example, in rates of child protection plans or registrations and out-of-home care. Previous research in the midlands region of England (Bywaters; Bywaters et al.) has detailed key aspects of the relationship between levels of neighbourhood deprivation and intervention rates. This paper reports further evidence from the study examining the intersection of deprivation with aspects of id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 19 publications
(44 reference statements)
4
61
0
1
Order By: Relevance
“…Trocmé et al (2014) found that over a ten year period the rate of urgent child protection referrals (any abuse of children aged under 5, physical abuse requiring medical attention, or sexual abuse) were unchanged, whilst investigations because of concerns about the well-being of children, often because of concerns about neglect and emotional abuse, more than doubled. A similar pattern is seen (Bywaters et al 2014a). Additionally, the evidence on individualised interventions to prevent further neglect and emotional abuse is sparse (Glaser et al, 2012).…”
Section: Child Protection Processmentioning
confidence: 80%
“…Trocmé et al (2014) found that over a ten year period the rate of urgent child protection referrals (any abuse of children aged under 5, physical abuse requiring medical attention, or sexual abuse) were unchanged, whilst investigations because of concerns about the well-being of children, often because of concerns about neglect and emotional abuse, more than doubled. A similar pattern is seen (Bywaters et al 2014a). Additionally, the evidence on individualised interventions to prevent further neglect and emotional abuse is sparse (Glaser et al, 2012).…”
Section: Child Protection Processmentioning
confidence: 80%
“…It is important for social workers to understand the effects of structural conditions, such as poverty, racism, or colonization on the presenting problems for families in the child welfare system (Hyslop, , Bywaters et al, ). In this study, the financial and poverty‐related issues impacting on the family were identified by both groups as a cause of the family problems, showing some awareness of the effects of structural factors relating to poverty on family life.…”
Section: Discussionmentioning
confidence: 99%
“…Child welfare inequalities can be defined as “unequal chances, experiences and outcomes of child welfare that are systematically associated with social advantage/disadvantage” (Bywaters, , p. 4). They may be further defined in relation to ethnicity as those inequalities that reflect differences “in the nature of child welfare interventions or provisions for parents and/or children across different social groups or identities” (Bywaters, Brady, Sparks, & Bos, , p. 452).…”
Section: Inequalities Disproportionality and The Risk‐bias Debatementioning
confidence: 99%
“…As a Behaviour Services Officer (white female) in the Coastal LA emphasised:
… a lot of it's about class and deprivation, perhaps the understanding, you know. The majority of teachers come from very similar backgrounds … their expectations of social niceties and how you interact with people is in a certain way … 'cause there's lots of values involved here that's quite – complicated.
She continued:
So, I think it's interesting because I can think of children that do exactly the same thing in school, and the school will work with them far longer and not exclude them, whereas if you've got a very difficult family with a parent coming and screaming and shouting at you …
Some professionals argued that poor families were no more likely to be “troubled” than middle‐class families, but that more affluent families were better able to conceal their difficulties (Bywaters, Brady, Sparks, & Bos, ):
… I think middle‐class parents are better at hiding that or better – not hiding it but, they're better from you know maintaining that it's all OK; whereas if you're working with a parent in this [deprived] suburb if something awful happened; say social services have been round the night before you know; it's all kicked off in the neighbourhood …. (Learning Mentor Co‐ordinator, Coastal LA)
…”
Section: Intersecting Socio‐economic (Dis)advantage and Sendmentioning
confidence: 99%